Influence of Role Identity and Collective Identity on Japan's Policy on Providing Official Development Assistance (ODA) to India - Tursina, Zahidiyah Ela; Soesilowati, Sartika; Susanto, Siti Rochmawati (Dauliyah: Journal of Islam and International Affairs, 2023)
Based on OECD data in 2019, Japan made India the first largest recipient of Japanese Official Development Assistance (ODA) in the world. This priority shows that for Japan, India is a very strategic country, causing Japan to give great priority to India. Moreover, many academics tend to view Japan as providing ODA assistance because Japan has political, economic, and other interests. However, this study attempts to use a constructivist perspective, which is a perspective that tends to look at the intrinsic values, such as the role of identity. Based on this research, the authors argue that Japan gives high priority  Japan's ODA assistance to India for several reasons. The first reason is that Japan wants to strengthen its role identity as a country that cares about development in developing countries. This has resulted in Japan trying to be very active in providing ODA assistance so that development conditions, especially in the economic sector in India, are getting better. Furthermore, the second reason, Japan provided Japanese ODA assistance to India because Japan’s view  is Japan had the same collective identity as India. Japan and India have a collective identity as countries that adhere to an open economy and as countries that want to have a big role in economic development in the Indo-Pacific region.